2022
DOI: 10.3390/nu14132766
|View full text |Cite
|
Sign up to set email alerts
|

The Current Findings on the Impact of Prenatal BPA Exposure on Metabolic Parameters: In Vivo and Epidemiological Evidence

Abstract: Metabolic syndrome (MS) is a multifactorial disease entity and is not fully understood. Growing evidence suggests that early exposure to bisphenol A (BPA) is a significant risk factor for the development of metabolic diseases. BPA is a monomer used in the manufacturing of polycarbonate plastics, thermal receipt paper, and epoxy resins. Owing to its widespread use, BPA has been detected in human fluids and tissues, including blood, placental breast milk, and follicular fluid. In the present review, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…For example, exposure to bisphenol A (BPA), a chemical found in some plastics, has been associated with an increased risk of MetS in adolescents. BPA can disrupt hormone signaling pathways, leading to alterations in glucose and lipid metabolism, which are components of MetS ( Trasande et al, 2012 ; Wu et al, 2020 ; Abulehia et al, 2022 ).…”
Section: Adolescencementioning
confidence: 99%
“…For example, exposure to bisphenol A (BPA), a chemical found in some plastics, has been associated with an increased risk of MetS in adolescents. BPA can disrupt hormone signaling pathways, leading to alterations in glucose and lipid metabolism, which are components of MetS ( Trasande et al, 2012 ; Wu et al, 2020 ; Abulehia et al, 2022 ).…”
Section: Adolescencementioning
confidence: 99%
“…A substantial body of literature has revealed that higher exposure to BPA can negatively affect human health ( 65 , 66 ). However, other studies have also revealed that the effect of prenatal BPA exposure on metabolic outcomes is often monotonic, with different doses of exposure having various influences on metabolic parameters ( 67 ). Our finding, which did not align with most existing literature, could be partially explained by several factors, including the fact that we estimated MRS using an average of four metabolic parameters: waist circumference, fasting glucose, lipids, and blood pressure measures.…”
Section: Discussionmentioning
confidence: 99%
“…One such chemical is BPA. Human exposure to BPA has been linked to adverse health effects including obesity (20). In rodents, fetal BPA exposure causes the size of adipocytes increase with age, resulting in a larger body fat percentage (21).…”
Section: Introductionmentioning
confidence: 99%